2016
DOI: 10.1037/tps0000054
|View full text |Cite
|
Sign up to set email alerts
|

Virgin soil in irony research: Personality, humor, and the “sense of irony”.

Abstract: he aim of the paper is fourfold: (a) show why humor scholars should study irony, (b) explore the need for considering interindividual differences in healthy adults' irony performance, (c) stress the necessity for developing tools assessing habitual differences in irony performance, and (d) indicate future directions for joint irony and humor research and outline possible applications. Verbal irony is often employed with a benevolent humorous intent by speakers, but can also serve as a means of disparagement hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Thus, perhaps not despite but rather because of the more elaborate, ecologically valid narrative of the video sequence and the resulting text messages of different forms of irony, the stereotypical occupation might just not have been so central than in short written text vignettes without much more other information. This would be in line with the results of Bruntsch et al (13), who, taking an extreme position, considered most contextual information simply as “noise” that distracts rather than serves as an additional resource for interpretation. The present research could not control for this hypothesis because all the stimuli were embedded in one stereotypical context.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, perhaps not despite but rather because of the more elaborate, ecologically valid narrative of the video sequence and the resulting text messages of different forms of irony, the stereotypical occupation might just not have been so central than in short written text vignettes without much more other information. This would be in line with the results of Bruntsch et al (13), who, taking an extreme position, considered most contextual information simply as “noise” that distracts rather than serves as an additional resource for interpretation. The present research could not control for this hypothesis because all the stimuli were embedded in one stereotypical context.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research has repeatedly linked mentalization or ToM abilities to impairments in irony comprehension, particularly in investigating reasons for decreased irony comprehension in clinical populations, with the most research available for autism (1, 30, 106, 109), schizophrenia (59, 110112), and related personality traits in healthy populations (1012, 113). Bruntsch et al (13) emphasized a high interindividual variance in irony comprehension even in healthy populations and suggested several personality traits (schizotypy, histrionic self-presentation, sense of humor, self-esteem, and gelotophobia) as potential explanations for this variance. These findings raise the question as to what degree personality traits or psychopathologic characteristics are distinct from or overlap with mentalizing abilities in irony processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the multiple definitional problems and operational challenges resulting from lack of any specific measure of irony, it is not surprising that research on irony brings conflicting and contradictory results. However, differences in irony perception might also result from the simple fact that we differ in how we see the world, what we like about it and how we describe it; this may explain why there is systematic variance in irony detection performance (Bruntsch et al, 2016 ). Previous research by Milanowicz ( 2013 ) showed that that men would use irony with the aim to amuse others, to make fun, and to be perceived as funny, but women would rather use ironic comments to show their disapproval and smuggle in more anger and meanness.…”
Section: Introductionmentioning
confidence: 99%